The new dynamics ofhigher education - González Sarmiento, Oiga (2009)
The goal of this article to explore the new dynmics of Higher Education base don the study of discoveries and conclusions made during the Second World Conference of Higher Education in July 2000. The internationalization, regionalization and globalization; research and innovation and also higher education in the African continent as a subject